The Existence Of The Sale And Purchase Agreement (PPJB) As Authentic Evidence Tool Based On Government Regulation No. 24 Of 2016 On The Position Rules Of Land Deed Official Position In Cilacap Regency - Basuki Basuki; Wildan Auliya; Ngadino Ngadino (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2020)
The purpose of this study was to: 1) To analyze the implementation of the Agreement manufacture Sale and Purchase of Land by the Land Deed Official (PPAT). 2) To analyze the existence of the Sale and Purchase Agreement (PPJB) as Authentic Evidence based on Government Regulation No. 24 of 2016 Concerning the Rules of Land Deed Official Position in Cilacap Regency. 3) To know and analyze the process of land registration with the Sale and Purchase Agreement (PPJB) as Authentic Evidence.This study using sociological or empirical juridical approach. In sociological juridical approach of law as law in action, described as a social phenomenon that is empirical, descriptive analysis specifications. The data collection was obtained by interview and literature.The research results are: 1) In the implementation of the keel PPJB included power from seller to buyer to sign the Sale and Purchase Agreements, so that the signing of the Sale and Purchase Agreements do not require the presence of the seller. PPJB is not paid, the payment is made if the selling price received by the seller has not paid off. In the chapters PJB not paid at least the specified amount of advance paid at the time of signing the deed of CHD, ways or terms of payment, when repayment and the agreed sanctions if one party defaults. PJB not paid off must also be followed by AJB at settlement. 2) the PPJB is binding for both parties (seller and buyer) as well as for the heirs or assigns who died.Keywords: PPJB; Authentic Evidence; Deed of Sale and Purchase.